Bulk plasmon‐polaritons in hyperbolic nanorod metamaterial waveguides. Issue 3 (9th April 2015) - Vasilantonakis, Nikolaos; Nasir, Mazhar E.; Dickson, Wayne; Wurtz, Gregory A.; Zayats, Anatoly V.
<x xml:space="preserve">Abstract</x> The waveguiding properties and mode structure of planar anisotropic metamaterial waveguides are characterized experimentally and theoretically. The extraordinary modes, originating from bulk plasmon polaritons of the metamaterial with hyperbolic dispersion, are shown to exhibit low or negative group velocity and high effective refractive indices (up to 10), allowing a deep‐subwavelength‐size single mode waveguides. The results are important for understanding of the enhanced nonlinear, sensing and Purcell properties of such metamaterials.